Functional Characterization of Olfactory Proteins Involved in Chemoreception of Galeruca daurica - Ling Li; Wen-Bing Zhang; Yan-Min Shan; Zhuo-Ran Zhang; Bao-Ping Pang (Frontiers in Physiology)
Odorant-binding proteins (OBPs) and chemosensory proteins (CSPs) play a fundamental role in insect olfaction. Galeruca daurica (Joannis) is a new pest with outbreak status in the Inner Mongolia grasslands, northern China. In this study, six olfactory protein genes (GdauOBP1, GdauOBP6, GdauOBP10, GdauOBP15, GdauCSP4, and GdauCSP5) were cloned by RACE and expressed by constructing a prokaryotic expression system. Their binding affinities to 13 compounds from host volatiles (Allium mongolicum) were determined by fluorescence-binding assay. In order to further explore the olfactory functions of GdauOBP15 and GdauCSP5, RNA interference (RNAi) and electroantennogram (EAG) experiments were conducted. Ligand-binding assays showed that the binding properties of the six recombinant proteins to the tested volatiles were different. GdauOBP6, GdauOBP15, GdauCSP4, and GdauCSP5 could bind several tested ligands of host plants. It was suspected that GdauOBP6, GdauOBP15, GdauCSP4, and GdauCSP5 were related to the host location in G. daurica. We also found that there were different EAG responses between males and females when the GdauOBP15 and GdauCSP5 genes were silenced by RNAi. The EAG response of G. daurica females to 2-hexenal was significantly decreased in dsRNA-OBP15-injected treatment compared to the control, and the dsRNA-CSP5-treated females significantly reduced EAG response to eight tested host volatiles (1,3-dithiane, 2-hexenal, methyl benzoate, dimethyl trisulfide, myrcene, hexanal, 1,3,5-cycloheptatriene, and p-xylene). However, the EAG response had no significant difference in males. Both GdauOBP15 and GdauCSP5 may have different functions between males and females in G. daurica and may play more important roles in females searching for host plants.